Work Measurement as a Generalized Quantum Measurement - Roncaglia, Augusto Jose (2014)
We present a new method to measure the work w performed on a driven quantum system and to sample its probability distribution P ( w ) . The method is based on a simple fact that remained unnoticed until now: Work on a quantum system can be measured by performing a generalized quantum measurement at a single time. Such measurement, which technically speaking is denoted as a positive operator valued measure reduces to an ordinary projective measurement on an enlarged system. This observation not only demystifies work measurement but also suggests a new quantum algorithm to efficiently sample the distribution P ( w ) . This can be used, in combination with fluctuation theorems, to estimate free energies of quantum states on a quantum computer.